Effects of mineral nutrition on inter-and intraspecific interference of peanut (Arachis hypogaea L.) and hairy beggarticks (Bidens pilosa L.) - Yamauti, Micheli Satomi [UNESP]; Da Costa Aguiar Alves, Pedro Luis [UNESP]; Bianco, Silvano [UNESP] (My University, 2012)
The present work was carried out to study the effects of mineral nutrition on peanut (Arachis hypogaea L) cv. IAC Runner-886 and hairy beggarticks (Bidens pilosa L.) growth, when submitted to inter-and intraspecific competition. The treatments consisted of two peanut plants per pot, two hairy beggarticks per pot and one plant of each species per pot. The plants were nourished with Hoagland and Arnon (1950) complete solution, or without potassium, or without phosphorus or without nitrogen. Sixty days after planting, no inter-or intraspecific competition effect on growth characteristics of peanut was verified and nutrition was not a limiting factor to the culture. No interaction between competition and nutrition effects was observed for both species. The weed suffered more negative effects from intraspecific competition and nutrition. The absence of N had a pronounced effect compared to the other elements, resulting in a reduction in all the evaluated characteristics. The deficiency of nutrients and competition affected the weed more than the crop, showing that peanut was more competitive than hairy beggarticks.